2014
DOI: 10.1179/2046905514y.0000000144
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D in adolescent females – an analytical cohort study in the United Arab Emirates

Abstract: The finding of a high prevalence of hypovitaminosis D in adolescent females in UAE is of serious concern for their health and that of their infants during their reproductive lives. Adolescent girls with a similar social and cultural background currently living in less sunny, industrialised countries might also be at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 43 publications
4
22
0
4
Order By: Relevance
“…In contrast, another study realized in Germany found that serum concentrations of individuals varied according to factors like the seasons, living in an urban or rural environment and the body mass index, in addition to time spent in sunny regions and Our results demonstrate that gender may be a determining factor that is strongly associated with vitamin D deficiency, since female adolescents had higher prevalence than males. Similar results have been found in other studies around the world (25,29). A recent cohort study conducted in the United States showed that in a model adjusted for several variables similar to ours, male participants had higher concentrations of 25 (OH) D over time when compared to females (30).…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, another study realized in Germany found that serum concentrations of individuals varied according to factors like the seasons, living in an urban or rural environment and the body mass index, in addition to time spent in sunny regions and Our results demonstrate that gender may be a determining factor that is strongly associated with vitamin D deficiency, since female adolescents had higher prevalence than males. Similar results have been found in other studies around the world (25,29). A recent cohort study conducted in the United States showed that in a model adjusted for several variables similar to ours, male participants had higher concentrations of 25 (OH) D over time when compared to females (30).…”
Section: Discussionsupporting
confidence: 78%
“…Indeed our observation that adolescent residing in Dubai have much higher percentage of vitamin D deficiency than expected, has been seen before by a group of investigators in Al-Ain ,United Arab Emirate, they found majority of young Emirati girls attending public school, aged between 11-18year, were deficient in Vitamin D [21].…”
Section: Discussionsupporting
confidence: 66%
“…This study supports the previous results of very high Hypovitaminosis D in U.A.E. females [3,19,28]. Other significant result noticeable is that dietary Vitamin D is not linked to Vitamin D status in general population of Emarati females from Abu Dhabi, and this was also observed in previous studies in university sample from Abu Dhabi [2], hence supplement use might me be the best way to achieve Vitamin D sufficient levels in this temperate country females.…”
Section: Discussionsupporting
confidence: 80%